MENINGKATKAN KEPERCAYAN DIRI PESERTA DIDIK KELAS VII DENGAN MODEL TEAM GAMES TOURNAMENT (TGT) BERBANTUAN PUZZLE PADA MATERI KONDISI WILAYAH INDONESIA - Christy, Herica; Dian Ayu Larasati; Agus Warsito (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to measure the improvement of students confidence and improvement of teacher teaching skills the seventh grade students at SMPN 50 Surabaya. This classroom action research was carried out in two cycles. The result of this research shown there are significant improvement of Students confidence in learning realm of attitude at the pre-cycle level was 39% as a not good category, after doing the research in the cycle I it changed into 69% as a good enough category and increased more in the cycle II to be 84% as a good category. The management of Teams Games Tournament model learning also increased in cycle I 77% as a good category to 87% as a good category in cycle II. The results of the pretest obtained an average score of 51 with the fair category and an increase in the postest which obtained an average score of 84 with the good category. It proves that used of Teams Games Tournament model use puzzle media can improve attitude self confidence in seventh grade students at SMPN 50 Surabaya.